M-health and telemedicine: are people ready for the future? A real-world survey. (25th November 2020) - Dossi, F; Marini, A; Sanna, G.D; Saba, P.S; Parodi, G
Abstract: Background: Many scientific societies highlight the importance of using e-Health and Telemedicine in everyday life. Are patients truly ready for this changing scenario in the cardiovascular field? Considering the current limited evidence on this topic we conducted a real-world data analysis in a rural area. Purpose: The aim of the present study was to assess the attitude of a rural area population towards the use of m-Health and Telemedicine for the improvement of cardiovascular healthcare-organization and prevention. Methods: An observational cross-sectional study, surveying 200 adult-subjects, with a multiple-choice questionnaire, was carried out by the authors during local health-fair events. We gathered self-reported demographics, digital skills, attitude towards telemedicine, and data regarding primordial, primary and secondary cardiac prevention, along with the strengths and the weaknesses of m-Health use. Results: Of the 200 surveyed subjects, only 179 [90%] completed the poll. Overall, 40% [n=71] appeared to be aware of telemedicine and 86% [n=154] stated to be interested in its use for everyday health-organization and cardiovascular prevention. No significative difference emerged regarding basic and advanced technological skills after subject stratification based on the education level, residence or age, except for the oldest subjects (i.e. over 80 years of age) which resulted less technologically skilled [p<0.05]. According to the respondents, Personal Computer, smartphone and wearable devices were considered useful tools to improve treatment adherence [median value: 4 out of 5 - IQR 4–5], save time [median value: 4 out of 5 - IQR 4–5] and develop a tailored treatment approach [median value: 4 out of 5 - IQR 1–5]. Nonetheless, m-Health was unknown to half of the respondents; in fact, only 48% [n=86] of the interviewed subjects were aware of its existence and 35% [n=63] affirmed to use apps for a preventive purpose on a daily basis. Otherwise, the large majority of subjects reported to be interested in its use [75%, n=135]. Privacy issues emerged as a major concern for app users in the setting of primary and secondary prevention; while, only 19.4% of those using apps for primordial prevention showed the same degree of concern [p<0.05]. No other significative difference appeared among tested queries. Conclusions: Our unselected population showed good technological skills and looked with favour at the advantages of telemedicine in everyday health-management because it provides reliable and feasible tools to improve cardiovascular healthcare in rural areas. However, awareness of its existence remains limited, underlining the need for more effective advertising policies. Although privacy and reliability issues currently make m-Health less feasible for primary and secondary prevention, m-Health has proved to be an excellent tool for primordial prevention. Funding Acknowledgement: Type of funding source: None